Woman Oppression in Maxine Hong Kingston’s The Woman Warrior: Memoirs of a Girlhood Among Ghosts (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2017)
Abstrak Penelitianinimendiskusikanmengenai novel Maxine Hong Kingston yang berjudulThe Woman Warrior: Memoirs of a Girlhood Among Ghosts.Analisisiniberkaitandenganpenindasanwanitaterhadappemeranwanita di novel tersebut.Selainitu, penelitianinijugamendiskusikanmengenaitipeataubentukpenindasanwanitadanpengaruhpenindasanterhadapkehidupanpemeranwanita di novel tersebut.Tujuandaripenelitianiniadalahuntukmendeskripsikantipedaripenindasanwanita di novel The Woman Warrior: Memoirs of a Girlhood Among Ghosts danuntukmendeskripsikanpengaruhdaripenindasanterhadapkehidupanpemeranwanita di novel tersebut. Metode yang digunakandalamanalisisiniadalahpenelitiansastradenganpendekatanfeminis.Untukmenjawabmasalah yang ada, penelitianinimenggunakanbeberapateoridankonsepdariGayatriSpivak di tulisannya yang berjudulCan Subaltern Speakdandidukungolehahliterifeminislainnyaseperti Iris Young yang dieditulangolehHeldke and O’Connor. Denganmenggunakanpendekatanfeminis, data diambildari novel yang berjudulThe Woman Warrior: Memoirs of A Girlhood Among Ghosts oleh Maxine Hong Kingston (1976). Novel in merupakansalahsatu novel yang menceritakanbagaimanaperempuan China yang berimigrasikeAmerikadandiamenjadiwanita yang selaludiamsebagaisalahsatupengaruhdaripenindasanwanita.Penelitianinimenunjukkanbeberapabagiandaribukti yang mengidentifikasitipedaripenindasandanpengaruhdaripenindasanterhadapkehidupanpemeranwanita di novel tersebut. Kata Kunci: The Woman Warrior, Penindasanwanita, tipedaripenindasanwanita, pengaruhpenindasanwanita, feminis, Maxine Hong Kingston Abstract This study discusses Maxine Hong Kingston’s novel The Woman Warrior: Memoirs of a Girlhood Among Ghosts. This analysis is related to the woman oppression toward the female character in the novel. Besides that, this study also discusses the type or form of woman oppression and the impacts of oppression toward the female character’s life in the novel. The purpose of this study is to describe the type of woman oppression in The Woman Warrior: Memoirs of a Girlhood Among Ghosts and to describe the impacts of oppression toward the female character’s life in the novel. The method used in this study is using literary study with feminism approach. To analyze the existing topic, this study uses several theories and concepts by GayatriSpivak in her essay Can Subaltern Speak and supported by the other thinkers of feminism theory likes Iris Young which edited by Heldke and O’Connor. By using feminist approach, data were taken from the novel entitled The Woman Warrior: Memoirs of A Girlhood Among Ghosts by Maxine Hong Kingston (1976). This novel is one of the novels that tells how the Chinese woman who immigrates to America and she became silencing woman as one of the impacts of women oppression. This study shows several pieces of evidence which indicate the type of oppression and the impacts of oppression toward the female character’s life in the novel. Keywords: The Woman Warrior, woman oppression, type of woman oppression, the impacts of woman oppression, feminism, Maxine Hong Kingston.